MOTIVASI DALAM KONTEKS HUMAN RELATIONS - Mudzhira Nur Amrullah (Al-MUNZIR, 2015)
A well motivated employee, will provide a greater contribution to the effectiveness of the organization. If an employee is well  motivated, he/she  will show a government that is effective and it is the key to success for a leader in building companies/institutions/government he leads. There are five important things to consider in terms of human relations to increase employee motivation to achieve organizational goals, among others: 1) availability of feedback and effective listening process, 2) the existence of sincerity in implementing the tasks as his responsibility, 3) understanding the needs of subordinate employees, 4) use time appropriately and effectively, 5) using appropriate communication channels. At first glance, human relations seems to be an ordinary matter and easy to do, but actually it is not. Human relations is a dynamic thing and can not be separated from the human factor. The working relationship between superiors and subordinates in communicating duties and responsibilities or delegation of authority would be very difficult to perform if it is not accompanied by a good process of human relations. Whether we realize it or not, human relations can give positive effects on a person's motivation to work. Unapproppriate techniques which an employer used in communicating with subordinates (vertical communication) will result in decreased motivation of subordinates. This can happen because the motivation is closely linked with the implications received as a result of a communication. Key Words : Motivasi, komunikasi, human relations.